ANALISIS PERBANDINGAN SISTEM MONITORING JARINGAN BERBASIS WEB MENGGUNAKAN NTOPNG DAN ZABBIX DI SMP N 1 TAMANSARI - Arnold Parulian Situmorang (2021)
The computer network monitoring system is one of the technologies that helps the process of monitoring the condition of a computer network, in its implementation, there are still many people who do not understand this system, and also with the many choices of systems available on the market it will make it more difficult to choose which network monitoring system is the most suitable to apply. This research was conducted with the aim of comparing two monitoring systems that have a web interface, namely Zabbix and NTOPNG in terms of initial features, protocols, scalability and user usage. From the results of the analysis, the expected results are research that can be accessed from Zabbix and NTOPNG in its function as a system or network monitoring tool in terms of initial features, scalability, protocols and usage so that it can be used as a reference for readers who want to implement one of the systems studied in their own computer network.